The blended course design workbook : a practical guide - Linder, Kathryn E. (Stylus Publishing, LLC, 2017)
Providing a step-by-step course design process that emphasizes active learning and student engagement, this book will help instructors adapt traditional face-to-face courses to a blended environment by guiding them through the development of course goals and learning objectives, assignments, assessments, and student support mechanisms with technology integration in mind. It will also help instructors choose the right technologies based on an instructor's comfort level with technology and their specific pedagogical needs. The book will help each instructor who uses the text to develop a unique course by making choices about their course design based on student learning needs for their chosen topic and discipline.